Apatinib in patients with recurrent or metastatic adenoid cystic carcinoma of the head and neck: a single-arm, phase II prospective study. (May 2021) - Zhu, Guopei; Zhang, Lin; Dou, Shengjin; Li, Rongrong; Li, Jiang; Ye, Lulu; Jiang, Wen; Dong, Minjun; Ruan, Min; Yang, Wenjun; Zhang, Chenping
Background: Apatinib, a vascular endothelial growth factor receptor (VEGFR) blocker, has demonstrated encouraging antitumor activities and tolerable toxicities in various cancer types. Recurrent or metastatic adenoid cystic carcinoma of the head and neck (R/MACCHN) carries a poor prognosis, and treatment options are currently limited. This study was conducted to explore the antitumor activity and safety of apatinib in patients with R/MACCHN. Methods: In this phase II single-arm, prospective study, patients aged 15–75 years with incurable R/MACCHN received apatinib at a 500 mg dose once daily until intolerance or progression occurred. The primary endpoint was the 6-month progression-free survival (PFS) rate based on RECIST version 1.1. The secondary endpoints included response rate, overall survival (OS), and safety. Efficacy was assessed in all dosed patients with at least one post-baseline tumor assessment. Results: Among 68 patients treated with apatinib, 65 were evaluable for efficacy analysis, with a median follow-up time of 25.8 months. The 6-month, 12-month, and 24-month PFS rates were 92.3% [95% confidence interval (CI): 83–97.5%], 75.2% (95% CI: 61.5–84.0%) and 44.7% (95% CI: 32.3–57.5%), respectively. The objective response rate (ORR) and disease control rate (DCR), as assessed by investigators, were 46.2% (95% CI: 33.7–59.0%) and 98.5% (95% CI: 91.7–100.0%), respectively. The median duration of response was 17.7 months [interquartile range (IQR) 14.0–20.9]. The 12-month and 24-month OS rates were 92.3% (95% CI: 83.0–97.5%) and 82.3% (95% CI: 70–90.4%), respectively. The most common adverse events of grades 3–4 were hypertension (5.9%), proteinuria (9.2%), and hemorrhage (5.9%). One patient developed a fatal hemorrhage. Conclusion: An encouraging PFS, a high ORR, and a manageable safety profile were observed in this study. It seems that the administration of apatinib in R/MACCHN is likely to have a clinically meaningful therapeutic benefit and warrants further investigation. This study was prospectively registered in ClinicalTrials.gov (NCT02775370; date of registration: 17 May 2016; date of first patient enrollment: 25 May 2016)